Study on the evolution of macro and fine mechanical properties and the micro-mechanism of cement-stabilized steel slag and gravel base course - Wang, Yifei; Ji, Haojie; Xie, Haiwei; Jia, Yao; Zhao, Xuzhang; Jiang, Wei; Liu, Zunqing (Frontiers in Materials, 2025)
This study addresses the performance requirements of road base course materials under special climate conditions in Xinjiang by employing the volume mixing method to design cement-stabilized steel slag (SSA)-gravel mixture. Systematic analysis was performed for the effects of SSA dosage (0%–100%) on the mechanical properties, shrinkage characteristics, and durability of the mixture. The test results indicated that the mechanical properties of the mixture exhibited an increasing trend up to a certain point before decreasing with further increases in SSA dosage. Notably, the C-B-1 gradation demonstrated optimal mechanical properties at a 60% SSA dosage, achieving an unconfined compressive strength of 8.9 MPa at 7 days with a 3% cement dosage. The discrete element simulation in PFC3D showed that this gradation provided a more significant backbone embedded extrusion effect. Moreover, increasing the SSA dosage effectively reduced the dry shrinkage strain of the mixture, however, the excessive dosage (>60%) caused a considerable increase in temperature shrinkage strain. Regarding durability, the mixture with 60% SSA dosage exhibited the best frost resistance, achieving an unconfined compressive strength of 7.9 MPa and a BDR of 82.3% after 18 freeze-thaw cycles. Microstructural analysis indicated that Ca2+ and SO42- released by SSA not only promoted the formation of early-stage AFt but also aided in developing a dense C-S-H gel in the later stages, thereby synergistically enhancing the material strength and durability. These findings offer the theoretical basis and technical support for the optimized design of road base course materials in Xinjiang.